2018
DOI: 10.1016/j.redox.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Integrative metabolomics and transcriptomics signatures of clinical tolerance to Plasmodium vivax reveal activation of innate cell immunity and T cell signaling

Abstract: Almost invariably, humans become ill during primary infections with malaria parasites which is a pathology associated with oxidative stress and perturbations in metabolism. Importantly, repetitive exposure to Plasmodium results in asymptomatic infections, which is a condition defined as clinical tolerance. Integration of transcriptomics and metabolomics data provides a powerful way to investigate complex disease processes involving oxidative stress, energy metabolism and immune cell activation. We used metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 67 publications
1
49
0
2
Order By: Relevance
“…Our results corroborate the increase in KYN/TRP ratio in naturally acquired P vivax malaria, as demonstrated in human‐controlled P vivax infections . Also, our observations are consistent with recent studies that characterized serum metabolomics of Plasmodium ‐infected humans and nonhuman primates . IFN‐γ was shown to be essential for IDO1 induction, and mice genetically deficient for IDO1 were not protected against cerebral malaria in a P berghei ANKA (PbA) mouse model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results corroborate the increase in KYN/TRP ratio in naturally acquired P vivax malaria, as demonstrated in human‐controlled P vivax infections . Also, our observations are consistent with recent studies that characterized serum metabolomics of Plasmodium ‐infected humans and nonhuman primates . IFN‐γ was shown to be essential for IDO1 induction, and mice genetically deficient for IDO1 were not protected against cerebral malaria in a P berghei ANKA (PbA) mouse model.…”
Section: Discussionsupporting
confidence: 91%
“…18 Also, our observations are consistent with recent studies that characterized serum metabolomics of Plasmodium-infected humans and nonhuman primates. [30][31][32] IFN-γ was shown to be essential for IDO1 induction, 33 and mice genetically deficient for IDO1 were not protected against cerebral malaria 34 The increase of Tregs has been demonstrated in acute human and murine malaria infections. [12][13][14]36,37 Previously in P falciparum infections, it was demonstrated that IL-10 and Tregs cells frequencies are influenced by malaria incidence and by the number of malaria infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from P. vivax- infected patients also reveal that parasitemia is significantly associated with metabolites involved in lipid metabolism, an observation that may be tied to their intracellular growth ( Gardinassi et al, 2017 ). Conversely, in a study observing factors associated with pre-existing P. vivax immunity, semi-immune subjects exhibit increased levels of linoleate metabolites compared to naive subjects ( Gardinassi et al, 2018 ). The ability of an infected individual to respond to malaria treatment may also be tied to host lipids, where patients with lower levels of baseline glycerophosphocholines were more likely to develop chloroquine-resistant malaria after infection ( Uppal et al, 2017 ).…”
Section: Immune Evasion and Disease Severitymentioning
confidence: 99%
“…previous exposure (Gardinassi et al, 2018;Cordy et al, 2019). We recently observed that acute Plasmodium infection induced an IFN-γ-driven increment in serum kynurenines that correlated with an elevation in the frequency of circulating FoxP3 + T regulatory cells in a hypo-endemic Amazon region (Dos Santos et al, 2020).…”
Section: Discussionmentioning
confidence: 95%